Therapeutic itinerary of colorectal cancer patients treated in the state of Rio Grande do Sul - Foletto,Eliara Fernanda (2016)
Abstract Objectives The objective of the study was to evaluate the therapeutic itinerary of patients treated in a specialized center, including its trajectory in seeking treatment and their clinical and epidemiological characteristics. Methods This is a cross-sectional prospective descriptive study; patients with colorectal cancer aged over 18 years and who signed the consent form were included in the analysis. Tumor characteristics, such as staging and tumor features; epidemiological characteristics such as age, gender, profession and itinerary in the form of the number of clinical visits needed to obtain the diagnosis; the main symptoms; and mean time between diagnosis and onset of treatment were evaluated. Results 34% of patients initially sought primary care (first level of care in the public health system) and 50% were diagnosed in secondary care (second level of care in the public health system); the mean number of visits until obtaining a diagnosis was 2.5 times; and 52% of patients received palliative therapy and 40% had a stage IV diagnosis. Conclusions The mean time between the diagnosis and the onset of treatment is in line with the recommendations of the Ministry of Health of Brazil. However, it was found that the patients are unaware of the symptoms of the disease, since the mean time between the onset of symptoms until the decision to visit the doctor was 177 days – which may have been a determining factor for a diagnosis in an advanced stage of disease.